Can Illegal Investments be Classified as Gambling? An Analysis - Suwinto Johan (PDIH Untag Semarang, 2023)
Economic expansion has been accompanied by a tremendous increase in personal wealth in recent decades. As people’s wealth increases, so do their investment demands. The number of illegal investment cases is likewise rising quickly. Along with technological advancements, gambling has become more prevalent in addition to incidences of unlawful investment. Ponzi scheme-based online gaming is expanding quickly throughout society. The purpose of this study is to compare unlawful investment to gambling from a legal and economic standpoint. The normative juridical method is employed in this study. This study employs a secondary legal method and utilizes associated rules as secondary legal materials. The study’s findings suggest that unlawful investing and gambling have some similarities. Gambling and illegal ventures both provide high profits. Owners of funds run the risk of losing money through unlawful investments and gambling. Along with gaming, the legislature needs to control unlawful investment—enforcement of the law against illicit gamblers.